Aboveground Biomass and Litterfall of Natural Evergreen Forest in Eastern Region of Thailand - Glumphabutr, Parinya; Kaitpraneet, San (วารสารวนศาสตร์ไทย, 2022)
The total aboveground biomass and net primary production (∆Pn) of natural evergreen forests in eastern region of Thailand were studied in moist evergreen forest (MEF), hill evergreen forest (HEF) at Khao Khitchakut National Park, and in dry evergreen forest (DEF) at Khao Soi Dao Wildlife Sanctuary, Chanthaburi province during January 2000 to January 2001. In addition, litterfall of these forests was studied during January 2001 to December 2001. The results showed that the annual increment of aboveground biomass was estimated at 5.39, 20.08 and 2.58 ton ha-1 yr-1 for the MEF, DEF and HEF, respectively. The net primary production of the MEF, DEF and HEF were estimated to be 13.24, 28.91 and 7.46 ton ha-1 yr-1, respectively. The annual litterfall of the MEF, DEF and HEF were estimated as 7.85, 8.83 and 4.88 ton ha-1 yr-1, respectively. Litter was lowest in the rainy season (May-October), and highest in the dry season (November-April), this evidence related to water shortage, leading to leaf fall in dry season. In addition, litterfall showed clearly some evidence of a peak in early dry season (December), there were 1.73, 1.67 and 0.64 ton ha-1, respectively. Keywords: aboveground biomass, eastern region of Thailand, evergreen forest, litterfall, net primary production